The Impact of Information and Communication Technology on Enhancing Health Service Quality - Suwanto Suwanto; Normawati Normawati; Josep A. Ufie; Safrudin Bustam Layn (Univiversitas Dr. Djar Wattiheluw, 2025)
This study investigates how information and communication technology (ICT) can enhance health services at the Central Maluku District Health Office. The findings reveal that website and mobile applications, telemedicine, and GIS need infrastructure upgrades, improved technological literacy, enhanced data security, and training for medical staff. Social media is utilized to raise public awareness, while Electronic Medical Records (EMR) streamline administrative efficiency and coordination. However, management systems for clinics and hospitals are still inadequate, leading to long wait times and scheduling problems. On a positive note, digital reporting is advancing, allowing for real-time monitoring and analysis at RSUD Masohi.